Nuclear Arms Control in South Asia: Politics, Postures, and Practices - Dr Anum Riaz (CISS Insight Journal, 2025)
The book “Nuclear Arms Control in South Asia: Politics, Postures, and Practices,” authored by Zafar Nawaz Jaspal, PhD, is a scholarly study of the complicated dynamics of nuclear arms control in South Asia. The author is a Professor and Dean of the School of Politics and International Relations (SPIR) at Quaid-i-Azam University (QAU), Islamabad. The book is organized into three sections, i.e., Politics, Postures, and Practices. The structured approach deployed in this volume provides a comprehensive framework for analyzing the intricate interplay of political motivations, strategic postures, and practical measures within the theoretical context that shapes South Asia’s nuclear environment.